Integration of Oracle SOA Suite and Blockchain Technology: A Framework for Real-Time Financial Transaction Processing - Nagireddy Vasipally (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive framework for integrating blockchain technology with Oracle SOA Suite to facilitate secure and efficient real-time financial transactions. The proposed architecture leverages distributed ledger technology’s inherent security features alongside Oracle’s robust service orchestration capabilities to address prevalent challenges in traditional payment systems. Through systematic implementation and rigorous testing, the article demonstrates significant improvements in transaction processing speed, security, and regulatory compliance. The integration framework incorporates smart contracts for automated transaction validation, enhanced payment messaging protocols, and optimized data processing pipelines. The article indicates that this hybrid architecture effectively reduces transaction settlement times while maintaining data integrity and meeting industry regulatory requirements. The article contributes to the growing body of knowledge in enterprise integration architecture and provides valuable insights for financial institutions seeking to modernize their transaction processing systems.